Nonviolent conflict and civil resistance - Nepstad, Sharon Erickson; Kurtz, Lester R. (Bingley, U.K. : Emerald, 2012)
This special issue of Research in Social Movements, Conflicts and Change analyzes examples of nonviolent resistance from across the globe. It covers how regime changes, political movements and nonviolent unrest develop and then shape the political decisions of both civil society and the state. Section one is focused on the strategic interactions between nonviolent movements and the state. This includes discussions on the civil rights movement in Northern Ireland, youth movements in Post-Communist states and nonviolent Islamic movements in Turkey. The second and third sections examine regime conflicts and the global diffusion of nonviolent movements. Here chapters center on the Iranian Revolution, social psychological approaches to nonviolent civil resistance, the Palestinian human rights movements, the efforts of nonviolent INGOs and the Nashville civil rights movement. This volume is essential reading because it introduces new analytical concepts and theoretical frameworks for understanding nonviolent resistance, merging social movement scholarship with nonviolent studies in fresh and exciting ways.
Introduction / Sharon Erickson Nepstad, Lester R. Kurtz -- The paradox of reform : the civil rights movement in Northern Ireland / Gregory M. Maney -- Tactical interactions between youth movements and incumbent governments in postcommunist states / Olena Nikolayenko -- "Thou shall not protest!" : multi-institutional politics, strategic nonconfrontation and Islamic mobilizations in Turkey / Mustafa E. Gürbüz, Mary Bernstein -- Inside the iron cage of liberalism : international contexts and nonviolent success in the Iranian revolution / Daniel P. Ritter -- Beyond rational choice : ideational assault and the strategic use of frames in nonviolent civil resistance / John A. Gould, Edward Moe -- "Movement schools" and dialogical diffusion of nonviolent praxis : Nashville workshops in the southern civil rights movement / Larry W. Isaac, Daniel B. Cornfield, Dennis C. Dickerson, James M. Lawson, Jonathan S. Coley -- When your Gandhi is not my Gandhi : memory templates and limited violence in the Palestinian human rights movement / Matthew P. Eddy -- Organizing global nonviolence : the growth and spread of nonviolent INGOS, 1948-2003 / Selina Gallo-Cruz.
Print version record
Keywords: Political Science -- NGOs (Non-Governmental Organizations).; Political Science -- Peace; Political Science -- Political Process -- General; Politics & government; Non-governmental organizations (NGOs).; Nonviolence; Government, Resistance to; Social movements